2015
DOI: 10.1159/000380821
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of MRI after Fetal Anomalies Have Been Diagnosed by Ultrasound: Correlation with Postnatal Outcomes

Abstract: Objective: The aim of this study was to investigate the additional value of fetal magnetic resonance imaging (MRI) in the assessment and management of fetuses with abnormal findings on ultrasound. Methods: A total of 257 patients who had fetal MRI following the ultrasound diagnosis of a fetal anomaly, or were at high risk, were included. The patients were grouped by referral category for fetal MRI. Fetal MRI was compared to ultrasound in the detection of anomalies, i.e. whether additional findings were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
1
7
0
2
Order By: Relevance
“…Widespread acceptance into clinical practice occurred in the late 1990s after the introduction of fast MRI sequences, which obviated the need for maternal sedation to reduce fetal movement. Since then, several investigators have reported on the accuracy of fetal MRI compared with that of ultrasonography (US) in the diagnosis of congenital anomalies. More recently, a systematic review summarized the results of previous studies related to the prenatal diagnosis of central nervous system (CNS) anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread acceptance into clinical practice occurred in the late 1990s after the introduction of fast MRI sequences, which obviated the need for maternal sedation to reduce fetal movement. Since then, several investigators have reported on the accuracy of fetal MRI compared with that of ultrasonography (US) in the diagnosis of congenital anomalies. More recently, a systematic review summarized the results of previous studies related to the prenatal diagnosis of central nervous system (CNS) anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…İşte bu prenatal sonografik taramalarda bir anormallik saptandığında ultrasonografiye yardımcı veya ultrasonografik bulguları tamamlayıcı bir görüntüleme modalitesine ihtiyaç doğmaktadır (1)(2)(3). Manyetik rezonans görüntüleme (MRG); gebelikte güvenli olması, yüksek görüntü çözünürlüğünün sağladığı tanısal başarısı ve görüntülerin arşivlenebilmesi gibi avantajları ile bu ihtiyaca cevap verebilen en önemli diagnostik modalitedir (1,2,4).…”
Section: Bu Amaçla Yapılan Muayenelerin Temel Aracıunclassified
“…Abnormalities of the central nervous detected via fetal ultrasound often prompt a referral for a fetal magnetic resonance imaging (MRI) study, which can help clarify diagnosis. [1][2][3] Over the last 20 years, there has been greater recognition that Blake pouch cyst, vermian hypoplasia, and "classic Dandy-Walker malformation" exist along a continuum of abnormalities resulting from abnormal development of the posterior membranous area during fourth ventricular development 4,5 and are commonly referred as the Dandy-Walker continuum, Dandy-Walker spectrum, or Dandy-Walker complex. Outcome in these conditions is variable.…”
Section: Introductionmentioning
confidence: 99%